CO2 capture enhancement by encapsulation of nanoparticles in metal–organic frameworks suspended in physical absorbents. (March 2023) - Xu, Ronghuan; Ahn, Hyungseop; Kim, Seonggon; Lee, Jae Won; Kang, Yong Tae
Abstract: In this study, CO2 nanoabsorbents composed of encapsulated Fe3 O4 nanoparticles in metal-organic frameworks (MOFs) and methanol, are developed to overcome the limitations of conventional CO2 sorbents. The polyvinylpyrrolidone-functionalized Fe3 O4 nanoparticles encapsulated in (Zn)MOF-74 [Zn2 (DOBDC), DOBDC = 2, 5-dihydroxyterephthalic acid] are dispersed in the methanol. Compared with pure methanol, CO2 absorption and regeneration performances of Fe3 O4 @ (Zn)MOF-74/methanol are improved by 13.07% and 16.25% (Abs.: 0.84 g-CO2 /L -solvent and reg.: 0.77 g-CO2 /L -solvent), respectively, at optimum conditions of 0.01 wt%. Cyclic stability experiments exhibit that the performance of Fe3 O4 @ (Zn)MOF-74/methanol can preserve 93.76% of their initial capacities. It is finally concluded that the absorption performance is improved by hydrodynamic and shuttle effects while the CO2 sorbent regeneration performance is enhanced by metal-organic heat carriers (MOHCs) and nucleation from the surface of nanoparticles by introducing Fe3 O4 @ (Zn)MOF-74 nanoparticles. Highlights: Nanoabsorbents are developed by MOF encapsulated with Fe3 O4, and methanol. The thermophysical property of nanoabsorbents is improved by Fe3 O4 encapsulation. wt% nanoabsorbents exhibit the highest absorption and regeneration performance. The CO2 absorption and regeneration mechanisms are proposed.